Evidence for weak collective pinning and δl pinning in topological superconductor CuxBi2Se3. (11th July 2018) - Li, M T; Fang, Y F; Sun, Z; Zhang, J C; Lin, C T
Abstract: We investigated the vortex pinning behavior in the single crystal topological superconductor Cu0.10 Bi2 Se3 with a pronounced anisotropic peak effect. A weak collective pinning regime is clarified from the power-law behavior in and the small critical current density ratio of ~ 10 −5 ( is the critical current density, is the depairing current density). The spatial variation of the charge-carrier mean free path induced pinning is evidenced and probably results from the well-defined atomic defects. Within the framework of collective pinning theory, we computed the values of the correlated length and volume at 1.8 K, which start declining prior to the onset field of the peak effect, demonstrating the vortex lattices already suffered a preferential collapse ahead of the peak effect turns up. Thus, the peak effect can be understood by elastic moduli softening near the upper critical field . We suggest Cu x Bi2 Se3 is a prototype topological material for investigating the vortex pinning dynamics associated with the peak effect phenomenon.